Resveratrol as a Therapy to Restore Neurogliogenesis of Neural Progenitor Cells Infected by Toxoplasma gondii - Bottari N.B. (2019)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature.The intracellular protozoan Toxoplasma gondii may cause congenital toxoplasmosis and serious brain damage in fetus. However, the underlying mechanism of neuropathogenesis in brain toxoplasmosis remains unclear. For this study, neural progenitor cells (NPCs) were obtained from embryo telencephalons (embryonic day 13) and induced to proliferation in the presence of growth factors (GFs). For gathering insights into the biological effects of resveratrol (RSV) on neurogenesis, this study aimed to investigate effects of RSV concentrations (0.1 to 100 μM) on proliferation, migration and differentiation of NPCs infected by T. gondii. T. gondii infection increased the presence of cells in Sub G1 phase, reducing the global frequency of undifferentiated cells in S and G2/M phases of cell cycle and reduced cell viability/mithochondrial activity of infected NPCs. Moreover T. gondii stimulated neural migration and gliogenesis during neutral differentation. However, the treatment with RSV stimulated cell proliferation, restored cellular viability of infected NPCs and exerted an inhibitory effect on gliogenesis of infected NPCs favorecing neuronal maturation during toxoplasmosis infection. Thus, we have successfully to demonstrated that RSV is promising as therapeutic for congenital toxoplasmosis.